3.0k views
2 votes
14y - (y - 2) + 5(y + 9)

User Timotimo
by
5.6k points

2 Answers

4 votes

Answer:

y = -2 11/18 or y = -2.6111 repeating

Explanation:

14y -(y - 2) + 5(y + 9)

Distribute the negative (-) to (y - 2)

Distribute the five (5) to (y + 9)

14y -y + 2 + 5y + 45

Combine like terms

18y + 47 = 0

-47 = -47

18y = -47

18y/18 = -47/18

y = -2 11/18

Hope this helps! :)

User Madhivanan
by
5.6k points
3 votes

Answer:

=18y+47

Explanation:

Let's simplify step-by-step.

14y−(y−2)+5(y+9)

Distribute:

=14y+−y+2+(5)(y)+(5)(9)

=14y+−y+2+5y+45

Combine Like Terms:

=14y+−y+2+5y+45

=(14y+−y+5y)+(2+45)

=18y+47

User Nolwww
by
5.1k points